PENGARUH KEPEMILIKAN INSTITUSIONAL, KOMISARIS INDEPENDEN, DAN KOMITE AUDIT TERHADAP TAX AVOIDANCE PADA SEKTOR PERUSAHAAN ENERGI DI INDONESIA TAHUN 2013-2022 - Rohmatun, Rohmatun (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2024)
This study aims to determine the effect of institutional ownership, independent commissioners, and audit committees on tax avoidance in the energy company sector in Indonesia in 2013-2022. The population used is panel data from the company's website and the Indonesia Stock Exchange (IDX). The research sample was determined by purposive sampling method, based on certain criteria relevant to the research objectives. Data collection is done through the documentation method, which involves secondary data from various sources. The data analysis technique used is multiple linear analysis, to identify the effect of independent variables on the dependent variable. dependent variable. The results of data processing show that institutional ownership has no effect on tax avoidance, while independent commissioners and audit committees have a negative effect. and audit committee have a negative effect. This means that the more independent commissioners independent commissioners and the more active the audit committee, the practice of tax avoidance will be reduced. practices will decrease. In conclusion, the role of independent commissioners and audit committees is very important in controlling tax avoidance at committee are very important in controlling tax avoidance in energy companies in Indonesia. in Indonesia.